2014
DOI: 10.1016/j.cgh.2013.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Serum Ferritin Levels Lack Diagnostic Accuracy for Liver Fibrosis in Patients With Nonalcoholic Fatty Liver Disease

Abstract: Background & Aim Series studies have associated increased serum levels of ferritin with liver fibrosis in patients with nonalcoholic fatty liver disease (NAFLD). We aimed to determine the accuracy with which measurements of serum ferritin determine the presence and severity of liver fibrosis, and whether combining noninvasive scoring systems with serum ferritin analysis increases the accuracy of diagnosis of advanced liver fibrosis. Methods We performed a retrospective analysis of data from 1014 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 29 publications
2
46
1
Order By: Relevance
“…Although it is known that ferritin is an acute-phase protein that can be increased in the context of systemic inflammation [45], it is not clear whether rifaximin can act directly on ferritin. Several studies using larger sample populations have shown that increased serum ferritin concentrations are associated with an increased risk of metabolic syndrome and diabetes [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is known that ferritin is an acute-phase protein that can be increased in the context of systemic inflammation [45], it is not clear whether rifaximin can act directly on ferritin. Several studies using larger sample populations have shown that increased serum ferritin concentrations are associated with an increased risk of metabolic syndrome and diabetes [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…23,27 Nevertheless, it was observed that noninvasive scores have diagnostic accuracy to distinguish between the presence or absence of advanced fibrosis, which did not increase with the addition of ferritin as a variable. 1 Cippà et al considered HPF as a predictor of hemochromatosis only for values above 2,000 mg/L. 23 Angulo et al showed that ferritin correlates positively with fibrosis severity but cannot be used to diagnose the presence or severity of liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…23 Angulo et al showed that ferritin correlates positively with fibrosis severity but cannot be used to diagnose the presence or severity of liver fibrosis. 1 The manifestations of MetS are influenced by visceral adiposity (VA), but unlike hyperinsulinemia and IR, VA does not determine greater severity of liver damage in patients with NAFLD. In contrast, adiponectin, an insulin-sensitizing adipokine characteristically decreased in obesity, is an independent risk factor for NAFLD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations